2016
DOI: 10.3892/mmr.2016.5015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RANKL-induced osteoclast differentiation through the downregulation of c-Fos and NFATc1 by Eremochloa ophiuroides (centipedegrass) extract

Abstract: Osteoclasts, derived from hematopoietic stem cells, are specialized macrophages and have a homeostatic role in skeletal modeling and remodeling with bone-forming osteoblasts. However, excessive osteoclast activity induces bone diseases, including osteoporosis, periodontitis and rheumatoid arthritis. Natural substances have received attention as therapeutic drugs in human diseases. In the current study, cells isolated from mouse bone marrow, and a mouse model, were used to determine the effect of centipedegrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…OSCAR is specifically expressed in early stage osteoclasts or in mature osteoclasts, and induces calcium activation to assist in the expression of RANKL-mediated NFATc1 (54). Similar to these results, the majority of osteoclast inhibition studies have reported that osteoclast-related genes are decreased by reduction of c-Fos and NFATc1 (55,56). OC-STAMP and ATP6v0d2 are expressed when the osteoclast precursor cells are fused, and when it is deficient, differentiation into osteoclasts is not completed.…”
Section: Discussionsupporting
confidence: 82%
“…OSCAR is specifically expressed in early stage osteoclasts or in mature osteoclasts, and induces calcium activation to assist in the expression of RANKL-mediated NFATc1 (54). Similar to these results, the majority of osteoclast inhibition studies have reported that osteoclast-related genes are decreased by reduction of c-Fos and NFATc1 (55,56). OC-STAMP and ATP6v0d2 are expressed when the osteoclast precursor cells are fused, and when it is deficient, differentiation into osteoclasts is not completed.…”
Section: Discussionsupporting
confidence: 82%
“…32 DC-STAMP is a key regulator of the cell fusion of osteoclasts controlled by NFATc1. 33 Then, osteoclasts attach to the bone matrix containing type 1 collagen and noncollagenous proteins. 34 In the process of mature osteoclast-mediated bone resorption, transcription of NFATc1 upregulates the release of osteoclast-related genes including CTS-K, TRAP, and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Choi et al also reported that the CGE extract did not inhibit the MAPK and NF-kB signaling pathways, but suppressed RANKL-induced c-Fos and NFATc1. It also affected the expression of osteoclast-related genes, such as OSCAR , MMP9 , and cathepsin K [ 44 ].…”
Section: Discussionmentioning
confidence: 99%